Presternal Dermoid Cyst Mimicking Lymphatic Malformation: a Case Report and Review of the Literature. Issue 1 (20th November 2012) - Berry, Tammy; Shetty, Anil; Delu, Adam; Barry, Marc; Berry, Ryan; Smidt, Aimee C.
<x xml:space="preserve">Abstract</x> Abstract: We describe an 11‐month‐old boy with an unusually large presternal mass present since birth. The large size, fluctuant properties, transillumination, compressibility, and imaging of this lesion were characteristic of a lymphatic malformation. Although four treatments with sclerotherapy markedly reduced its size, it was not until definitive treatment with surgical excision and the final pathology report that we arrived at the ultimate diagnosis of dermoid cyst. Dermoid cysts, although appearing along embryologic lines of closure, are rarely presternal. They are usually small, thick walled, and filled with sebaceous or keratinous fluid, which typically allows for clinical diagnosis, and show characteristic features on magnetic resonance imaging (MRI) and ultrasound. However, this case illustrates that dermoid cysts can appear in somewhat atypical locations, and imaging is not always diagnostic, so dermoid cyst should remain a part of the differential diagnosis for any lesion presenting midsternally, regardless of the size and imaging characteristics.